Physiopathological effects of noise: Recent approaches to the treatment of hearing loss - Küsen, Hande; Özdengül, Faik; Solak Görmüş, Z Işık; Şen, Aysu (Journal of Surgery and Medicine, 2022)
A significant problem can be exposure to noise, which is one of the negative effects of growing industry and production facilities around the world. Many individuals are exposed to high levels of noise at work, which causes problems. One of the most affected systems of exposure to noise is the auditory system. Hearing is damaged from exposure, such that individuals lose their sense of hearing. In the last 10 years, research has been done globally to prevent and treat noise-related hearing loss. When the data are examined, it can be seen there is protection and treatment for noise-induced hearing losses. The physiopathological effects of noise and new approaches are currently being examined.